2007
DOI: 10.1021/jo0711034
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Cyclopropanone Acetals with Alkyl Azides:  Carbonyl Addition versus Ring-Opening Pathways

Abstract: The Lewis acid-mediated reactions of substituted cyclopropanone acetals with alkyl azides were found to strongly depend on the structure of the ketone component. When cyclopropanone acetal was treated with alkyl azides, N-substituted 2-azetidinones and ethyl carbamate products were obtained, arising from azide addition to the carbonyl, followed by ring expansion or rearrangement, respectively. When 2,2-dimethylcyclopropanone acetals were reacted with azides in the presence of BF 3 •OEt 2 , the products obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Considering the biological relevance of β‐lactam derivatives, a particularly attractive transformation we were prompted to study is the formal [3+1] cycloaddition of cyclopropanones with nitrene equivalents to afford β‐lactams. An analogous Schmidt‐type rearrangement had previously been reported by Aubé and co‐workers using (1‐ethoxycyclopropoxy)trimethylsilane in the presence of organoazides and BF 3 ⋅OEt 2 , although only unsubstituted achiral β‐lactam derivatives could be obtained in low to moderate yield . In that work, the relatively harsh conditions required for equilibration to cyclopropanone likely led to multiple decomposition pathways.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Considering the biological relevance of β‐lactam derivatives, a particularly attractive transformation we were prompted to study is the formal [3+1] cycloaddition of cyclopropanones with nitrene equivalents to afford β‐lactams. An analogous Schmidt‐type rearrangement had previously been reported by Aubé and co‐workers using (1‐ethoxycyclopropoxy)trimethylsilane in the presence of organoazides and BF 3 ⋅OEt 2 , although only unsubstituted achiral β‐lactam derivatives could be obtained in low to moderate yield . In that work, the relatively harsh conditions required for equilibration to cyclopropanone likely led to multiple decomposition pathways.…”
Section: Resultssupporting
confidence: 66%
“…With general access to aw ide variety of highly reactive cyclopropanone precursors,w es ought to apply these substrates in strain-releasing rearrangements.C onsidering the biological relevance of b-lactam derivatives, [25] ap articularly attractive transformation we were prompted to study is the formal [3+ +1] cycloaddition of cyclopropanones with nitrene equivalents to afford b-lactams.A na nalogous Schmidt-type rearrangement had previously been reported by AubØ and coworkers using (1-ethoxycyclopropoxy)trimethylsilane in the presence of organoazides and BF 3 •OEt 2 , [26] although only unsubstituted achiral b-lactam derivatives could be obtained in low to moderate yield. [27,28] In that work, the relatively harsh conditions required for equilibration to cyclopropanone likely led to multiple decomposition pathways.Moreover,we sought to avoid organoazides in order to improve the applicability of the method on alarger scale.After evaluating various other nitrene equivalents, [11] it was found that simple hydroxylamines or their corresponding ethers could play the same role when the reaction was run in presence of aL ewis acid (Scheme 4).…”
Section: Synthesis Of B-lactams By Formal [3+ +1] Cycloadditionmentioning
confidence: 79%
“…The highly ring strained cyclopropanone (which is conveniently stored and used as a mixed ketal) also undergoes Schmidt chemistry to afford N -substituted β -lactams along with ethyl carbamates in about a 1 : 1 ratio (Scheme 7.9 ). 23,24 Presumably, the β -lactam is formed via the typical ring expansion mechanism described above. Ethyl carbamates are more mechanistically intriguing, requiring the formal loss of ethylene and N 2 followed by recombination of a silylated isocyanate with ethanol.…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
“…31,109 Simple azetidine -2 -ones 92 have also been obtained in moderate yield, along with carbamate esters 93 , from the boron trifl uoride catalyzed reaction of benzyl azides with a cyclopropanone acetal 91 . 110 The complex 94 has been suggested as an intermediate in the ring expansion reaction (Scheme 6.36 ).…”
Section: Azetidinonesmentioning
confidence: 99%
“…Scheme 6.34 Triaziridines 108Scheme 6.35 Azetidin -2 -ones from 4 -azidopyrrol -2(5 H ) -ones 109Scheme 6.36 Azetidin -2 -ones from a cyclopropanone acetal110 …”
mentioning
confidence: 99%